Legal Protection for Children Suffering from HIV/AIDS: Perspective of Classical Fiqh and Contemporary Fiqh - Reza Ramadhan; Nurul Hidayah (Postgraduate Programme of UIN Kiai Haji Achmad Siddiq Jember, 2020)
This research examines legal protection for children living with HIV/AIDS from the perspective of classical and contemporary fiqh and its implementation in the context of positive law in Indonesia. Classical fiqh emphasizes the importance of protecting the soul (hifz nafs) as one of the maqashids of sharia, while contemporary fiqh adopts a more flexible and humanist approach in dealing with modern challenges such as HIV/AIDS. This research uses a normative juridical method with a literature study approach, analyzing primary and secondary legal sources. The research results show that although Law Number 35 of 2014 concerning Child Protection has regulated special protection for children living with HIV/AIDS, its implementation in the field still faces various challenges such as social stigma and lack of public understanding. This research proposes an integration of classical and contemporary fiqh views to form a more holistic and inclusive national policy, as well as recommending increasing public education and empowering Islamic social and educational institutions to support the protection of children living with HIV/AIDS.